Communication Patterns in Acculturating Indigenous Peoples Culture in the Canggu Area North Kuta Bali - Riesma Yuniar Laksana Putri; Erfina Nurussa'adah (Jurnal Audience: Jurnal Ilmu Komunikasi, 2022)
This study aims to find out how the communication pattern in acculturating the culture of the people in Bali with socio-cultural studies conducted on migrants living in the Canggu area. Acculturation is a social process that arises when a group of people with a certain culture encounters elements from a foreign culture so that the elements of foreign culture are gradually accepted and reprocessed without causing loss of the original culture. Canggu is one of the favorite tourist spots for foreign tourists. Local residents call Canggu in North Kuta, Bali, known as Kampung Bule. Foreign tourists are so easy to find there, that's why this research was conducted in Canggu. The collection of data from this study was direct observation and later studied using the Fundamental Interpersonal Relationship Orientations or FIRO theory. Examples in this study are migrants and local residents to establish the pattern of communication between them. The results of the study show that the culture used by the local community towards everyone in the Canggu area, both foreign and domestic visitors, is a very strong dialect, as well as symbols of both verbal and nonverbal communication used by the local community.Keywords: Cultural Acculturation; Canggu; Interpersonal Communication